As You Law It - Negotiating Shakespeare (Volume 15) - Carpi, Daniela; Ost, François (De Gruyter, 2018)
Shakespeare was fascinated by law, which permeated Elizabethan everyday life. The general impression one derives from the analysis of many plays by Shakespeare is that of a legal situation in transformation and of a dynamically changing relation between law and society, law and the jurisdiction of Renaissance times. Shakespeare provides the kind of literary supplement that can better illustrate the legal texts of the sixteenth and early seventeenth centuries. There was a strong popular participation in the system of justice, and late sixteenth-century playwrights often made use of forensic models of narrative. Uncertainty about legal issues represented a rich potential for causing strong reactions in the public, especially feelings concerning the resistance to tyranny. The volume aims at highlighting some of the many legal perspectives and debates emplotted in Shakespearean plays, also taking into consideration the many texts that have been produced during the latest years on law and literature in the Renaissance.